Analisis Efektivitas dan Potensi Retribusi Daerah terhadap Pendapatan Asli Daerah (PAD) di Kota Banjarmasin - Amalia, Siti (PPJP ULM, 2018)
This study aims to find out how the potential of regional levies in the city ofBanjarmasin through the rate of growth and contribution by using a potential matrix,how is the contribution of acceptance of regional retribution to increase of originalregional income in Banjarmasin City, and how effectiveness level of attainment oflocal retribution levies in Banjarmasin City during 2012-2016. The results of the study using the potential matrix to see the potential ofregional levies through growth rates and these contributions show the average yieldof positive growth rate and its contribution is not possible, these results indicate thatthe potential of regional levies in Banjarmasin City during 2012-2016 fall into thedeveloping category. While the level of effectiveness of local retribution into thecategory very effective because the average value of efficacy of regional levies duringthe last five years is above 100%.